Cirrhosis, cellulitis and cats: a 'purrfect' combination for life-threatening spontaneous bacterial peritonitis from Pasteurella multocida. (12th November 2012) - Hey, Penelope; Gow, Paul; Torresi, Joseph; Testro, Adam
Abstract : Pasteurella multocida is a Gram-negative coccobacillus that colonises the upper airways of many animals, in particular, dogs and cats. It acts as an opportunistic infection in humans following an animal bite or scratch and is associated with soft tissue infections, septicaemia and pneumonia, particularly in patients with a compromised immune response, such as patients with liver failure. Spontaneous bacterial peritonitis (SBP) is a serious complication of cirrhosis with a death rate of 10–15%. We report a case of a 47-year-old man with cirrhosis who presented with life-threatening P multocida SBP and bacteraemia secondary to a lick from a cat to a cellulitic leg wound. This case highlights the potential severity of an infection from domestic animals and an otherwise innocuous organism in an immunocompromised host.